Fabrication of Poly(L-Lactic Acid)/Chitosan Scaffolds by Solid–Liquid Phase Separation Method for Nerve Tissue Engineering: An In Vitro Study on Human Neuroblasts. Issue 3 (May 2019) - Salehi, Majid; Farzamfar, Saeed; Bozorgzadeh, Shaghayegh; Bastami, Farshid
Abstract : Abstract: Polymeric scaffolds that support neural cell behaviors are attracting more attention. In the present study, solid–liquid phase separation technique is used to fabricate scaffolds made of poly(L-lactic acid) (PLLA) and chitosan (CS) blends to mimic both cellular microenvironment and anatomical structure of nerve tissue. The fabricated scaffolds favor characteristics of both natural and synthetic polymers. Different tests and assays including physical and mechanical ones (in vitro degradation rate, free radical release, hydrophilicity, and porosity measurements, microstructure observation, and mechanical tests) and cellular assays (cell attachment measurement and viability assessment) suggest that blend scaffolds prepared with this method support nerve cells for tissue engineering applications adequately and even better than scaffolds prepared with the same method but from pure PLLA or CS. Abstract : Supplemental Digital Content is available in the text